Simvastatin alleviates airway inflammation and remodelling through up‐regulation of autophagy in mouse models of asthma. Issue 3 (26th October 2016) - Gu, Wen; Cui, Rong; Ding, Tao; Li, Xiaoming; Peng, Juan; Xu, Weiguo; Han, Fengfeng; Guo, Xuejun
ABSTRACT: Background and objective: Statins have been widely used in inflammatory diseases including asthma, because of their anti‐inflammatory and immunomodulatory properties. It has been shown that simvastatin induces autophagy and cell death in some circumstances. However, the possible cross‐talk between simvastatin and autophagic processes in lung disease is largely unknown. Thus, we investigated the impact of simvastatin on airway inflammation and airway remodelling and the possible relationship of these processes to a simvastatin‐induced autophagic pathway in mouse models of asthma. Methods: Ovalbumin (OVA)‐sensitized and challenged mice were treated with simvastatin and sacrificed. The autophagy‐related proteins Atg5, LC3B and Beclin1 were quantified, as well as the autophagy flux in bronchial smooth muscle cells (BSMCs). The relationship between airway inflammation and the autophagic process was investigated. Results: We show that simvastatin treatment mediates activation of autophagy in BSMCs, which is correlated with airway inflammation and airway remodelling in mouse models of asthma. Simvastatin increases autophagy‐related protein Atg5, LC3B and Beclin1 expression and autophagosome formation in lung tissue. Simvastatin‐induced autophagy is associated with increased interferon‐gamma (IFN‐γ) and decreased IL‐4, IL‐5 and IL‐13 cytokines production in BSMCs, as well as reversed extracellular matrix (ECM) deposition. In contrast, autophagy inhibitor 3‐methyladenine (3‐MA) eliminates the therapeutic effect of simvastatin. Conclusion: These findings demonstrate that simvastatin inhibits airway inflammation and airway remodelling through an activated autophagic process in BSMCs. We propose a crucial function of autophagy in statin‐based therapeutic approaches in asthma. Abstract : The study shows that simvastatin contributes to inhibit airway inflammation and airway remodelling likely through activated autophagic process in bronchial smooth muscle cells (BSMCs) in mouse models of asthma.